THE EFFECT OF LEARNING EFFECTIVENESS, LEARNING INDEPENDENCE, LEARNING DISCIPLINE, AND LEARNING MOTIVATION ON UNDERSTANDING BASIC CONCEPTS OF COST ACCOUNTING AT UNIVERSITIES IN MEDAN WITH SELF EFFICACY AS MODERATION - Nadya Sanchristallove Lubis; Chris Belinda Zega; Riadi Riadi; Desy Astrid Anindya (SEAN Institute, 2023)
The purpose of this study was to prove whether there is an effect of the effectiveness of online learning, learning independence, learning discipline, and learning motivation on understanding the basic concepts of cost accounting at universities in Medan with self-efficacy as moderation that can strengthen understanding of the basic concepts of cost accounting. This study uses a type of quantitative research using the SPSS version 25.00 program. The sample of this study were students from 3 different universities in Medan, namely Prima Indonesia University, North Sumatra University, HKBP Nomensen University as many as 40 students who had taken cost accounting courses. Ddata collection method using a questionnaire.